Giant cribriform adenocarcinoma of the tongue showing PRKD3 rearrangement - Majewska, Hanna; Skálová, Alena; Weinreb, Ilan; Stodulski, Dominik; Dziadziuszko, Katarzyna; Stankiewicz, Czesław; Biernat, Wojciech (Polish Journal of Pathology, 2016)
Cribriform adenocarcinoma of the tongue and minor salivary glands (CAMSG) was first described 16 years ago. It typically presents as a mass at the base of the tongue with early spread to lymph nodes, but without potential for distant metastases. In the 2005 World Health Organization Classification of Tumors the entity was classified as a possible variant of polymorphous low-grade adenocarcinoma (PLGA). Since then, more than 40 cases have been described in the English literature. Recently, PRKD1-3 translocation was found in more than 80% of CAMSGs. In some of those cases ARID1A or DDX3X was the translocation partner. We reviewed 183 primary carcinomas of major and minor salivary glands, resected at the Medical University of Gdańsk, Poland, in the period 1992-2012, and identified only one case of CAMSG. A giant tumor developed at the base of the tongue in a 76-year-old man. The primary tumor was resected with multiple bilateral cervical lymph node metastases. The patient received radiotherapy but died 10 months after the surgery due to causes not related to the primary cancer. The tumor presented PRKD3 rearrangement as confirmed by FISH. As the tumor is extremely rare (it represented only 0.5% of salivary gland tumors in our series), the controversy on its nosological status is still unresolved. This is the first report in the world literature of a patient who died in the course of CAMSG.